The relationship between COVID‐19 and HLA in kidney transplant recipients, an evaluation of predictive and prognostic factors. Issue 2 (24th November 2021) - Ertosun, Mustafa Gökhan; Özkan, Özlenen; Darbaş, Şule; Özel, Deniz; BİLGE, Uğur and Sayin Ekinci, Nurten and Yilmaz, Vural Taner and Uçar, Fahri and Koçak, Hüseyin and Özkan, Ömer
Abstract: Introduction: The purpose of this study was to determine the predictive and prognostic factors for COVID‐19 infection and its relationship with human leukocyte antigen (HLA) in kidney transplant recipients. Material and method: Three hundred fifty kidney transplant recipients were included in the study. Recipients were divided into two groups: COVID‐19(+) (n = 100) and control (n = 250). The relationships between HLA frequencies, COVID‐19 infection, and prognostic factors (age, donor type, immunosuppression protocol, etc.) were then evaluated. Logistic regression analysis, heatmap, and decision tree methods were used to determine predictive and prognostic factors. The study was performed retrospectively. Results: Advanced age and deceased transplantation emerged as predictive of SARS‐CoV‐2 infection, while the presence of HLA‐A*11, the HLA match ratio, and high‐dose tacrolimus were identified as prognostic factors in kidney transplant recipients. HLA‐A10, HLA‐B*13, HLA‐B22, and HLA‐B*55 were shown to be associated with SARS‐CoV‐2 infection at univariate analysis, and HLA‐B*57, HLA‐DRB1*11, and HLA‐DRB1*13 at logistic regression analysis. Conclusion: HLA‐A10, HLA‐B*13, HLA‐B*55, HLA‐B*57, HLA‐DRB1*11, and HLA‐DRB1*13 were identified for the first time in the literature associated with SARS‐CoV‐2 infection in kidney transplant recipients.